Endogenous sex hormones and their associations with cardiovascular risk factors in post-menopausal women - (:unkn) unknown (SPRINGER, 2013)
Aims: Our aim was to understand the relationship between endogenous sex hormones and cardiovascular disease (CVD) risk factors in post-menopausal women. Materials and methods: Eighty-three post-menopausal women from a previous prospectively designed study were included. We analyzed endogenous sex hormones and biochemical parameters. Results: Levels of estradiol and free testosterone were higher in patients with metabolic syndrome. Estradiol correlated positively with interleukin-6 (IL-6), weight, body mass index (BMI), insulin, homocysteine, and homeostasis model assessment of insulin resistance (HOMA-IR). Free testosterone correlated positively with weight, waist circumference (WC), BMI, insulin, HOMA-IR and negatively with HDL and SHBG. DHEAS correlated only with HDL. FSH correlated negatively with age, weight, WC, hip circumference, BMI, systolic blood pressure, diastolic blood pressure, duration of menopause, fasting glucose, HDL, C-reactive protein, and insulin. LH correlated negatively with IL-6, age, WC, duration of menopause and SHBG. Conclusions: We identified endogenous estradiol and free testosterone as the strongest links to CVD risk. They can be used as biomarkers for CVD risk estimation. (C) 2013, Editrice Kurtis
Keywords: Cardiovascular disease; CRP; endogenous sex hormones; interleukin-6; postmenopausal women; C-REACTIVE PROTEIN; CORONARY HEART-DISEASE; METABOLIC-SYNDROME; ATHEROSCLEROSIS RISK; BINDING GLOBULIN; MARKERS; INFLAMMATION; TESTOSTERONE; RELEASE; GLUCOSE